Aplicación de marcos de trabajo ágil e implementación de nuevas tecnologías en empresas peruanas - Simon Alvan, Esteban (2022)
Since my professional career started, I have specialized mainly in two of the academic areas of the program: Information Technologies and Business Engineering. My work experience began with the first one, and I was able to lead processes such as the management of technological assets in a company in the energy sector. During this period, I was able to link the concepts learned at the University, particularly in terms of technical capacity, to the day-to-day experience managing the entire life cycle of assets ranging from the choice of cell phones for employees to servers and specialized software for the proper synchronization of the company with the National Interconnected Electrical System. After about a year I decided to change course to the second academic area mentioned above. I went on to work on projects of implementation of software solutions in a company dedicated to the manufacture, distribution and commercialization of beauty and personal care products. On this occasion I was able to learn a lot about the internal operations of a company because I worked with internal customers such as the areas of Human Resources, Legal, Business Planning, Finance, Audit, among others. And I understood how technology is present and contributes to each one of them. It was also there where I learned about agile frameworks, which allowed me to take the next step in my career. It is in the latter where I found something that I am passionate about, since it combines the development of socioemotional skills to achieve the formation of highperformance teams with the technical skills that allow to accelerate to the fullest the development and implementation of digital solutions that meet the needs of both external customers and for-profit and non-profit organizations.